Rainfall and temperature trends in the Altiplano Potosino Region, Mexico (1975-2015) - Rocha-Escalante, Hermann; Jaimes-Arredondo, Araceli; Cardona-Benavides, Antonio; Rodríguez-Cuevas, Clemente; Giácoman-Vallejos, Germán; Aceves-de Alba, Jorge; García-Arreola, María Elena; Cisneros-Almazán, Rodolfo (Tecnología y ciencias del agua, 2022)
The observed changes in the climate systems during the last decades have generated a growing popular concern, especially in the scientific world, which has led to a series of research on the causes and possible consequences of climate change. This is a topic of great interest worldwide, including in Mexico. The Altiplano Potosino Region, Mexico, is located in the northwestern part of the state of San Luis Potosi, Mexico, with an approximate area of 29 119 km2, with an annual rainfall lower than 400 mm and an annual average temperature of 17.5 °C. Groundwater is the main source of supply because surface runoff is limited. The objective of this study was to perform a time series analysis of the historical records of rainfall and temperature, at the meteorological stations located in the study region from the period 1975 to 2015, to identify spatial and temporal trends and patterns. For this, the non-parametric Mann-Kendall test was used. The results indicate both increased and decreasing trends in the annual and monthly periods for the variables analyzed. Trends suggest local behaviors. Monthly precipitation trends show increases in spring and summer, while they tend to decrease in autumn. Annual and monthly temperature trends show a greater variability spatial and temporal, where there are important annual variations because of the monthly changes; or there are monthly variations that are not yet reflected in an annual trend.